Electrochemical Immunosensor with Enhanced Stability for Sensitive Detection of α-fetoprotein Based on Pd@Ag@CeO2 as Signal Amplification Label. Issue 16 (1st January 2018) - Zhang, Xiaobo; Li, Yueyun; Lv, Hui; Gao, Zengqiang; Zhang, Chunyan; Zhang, Shuan; Wang, Yuebo; Xu, Zhen; Zhao, Zengdian
Abstract : In this work, Pd@Ag@CeO2 core@shell nanoparticles (NPs) were synthesized as signal amplified label to construct a sandwich-type electrochemical immunosensor for quantitative detection of α-fetoprotein (AFP). The Pd@Ag@CeO2 accelerated electron transfer efficiency of the sensing interface as well as increased the amount of secondary antibodies (Ab2 ) immobilized due to excellent conductivity and the large surface area. In particular, the Pd@Ag@CeO2 NPs could contribute synergetic catalytic performance with the good protection of noble metal NPs from CeO2 support shell. Furthermore, Au NPs supported microporous carbon spheres functionalized by 3-aminopropyltriethoxysilane (Au-APTES-MCS) was used to immobilize the primary antibodies (Ab1 ), owing to good electrical conductivity and favorable biocompatibility. On the basis of the enhanced stability and intensity of signal response, the developed immunosensor provided a linear ranging from 0.4 pg mL −1 to 100 ng mL −1 and a detection limit of 0.13 pg mL −1 for AFP detection. Meanwhile, it exhibited good reproducibility, high specificity, and long-term stability, which indicated that the proposed biosensor had potential application in clinical analysis.